Strategic Vigilance in Sports Clubs: Insights and Practices - A, Gaafar; A, Al-Droushi; M, Al Kitani; A, Al yaaribi; M, Sharshouh (Journal of Ecohumanism, 2024)
Objectives: This study explores the reality of strategic vigilance practices in sports clubs in Oman. Methods: A questionnaire was administered to a random sample of 162 participants which included members of boards of directors, club managers, sports activity directors, coaches, and players in Oman. Result: Institutions show significant gaps in competitor analysis and communication with authorities, leading to a shortage of technological expertise that negatively impacts service promotion. Sports institutions prioritize continuous service development to retain existing clients and attract new ones. Conclusions: The study revealed a need to promote a culture of strategic vigilance among all employees in sports institutions in Oman. It emphasizes the necessity of engaging marketing specialists to address weaknesses within the institutions and contribute to the development of marketing vigilance